The influence of organizational culture, leadership and human capital on organizational change of the Pesisir Bukit Camat office - Wazirman, Wazirman; Gusnadi, Herman; Neli, Hasvia; Sriwahyuni, Sriwahyuni (Institute of Computer Science (IOCS), 2024)
This study aims to see the effect of Organizational culture on organizational change at the Pesisir Bukit Camat Office. Leadership on organizational change at the Pesisir Bukit Camat Office. Human capital on organizational change at the Pesisir Bukit Camat Office. Organizational culture, leadership, and human capital jointly affect organizational change at the Pesisir Bukit Camat Office. The population in this study were all 32 employees of the Pesisir Bukit Camat Office. The technique of determining the number of samples using total sampling technique (the whole sample is 32. The results of this study indicate that Organizational culture has a positive influence on organizational change at the Pesisir Bukit Camat Office. Leadership has a positive influence on organizational change at the Pesisir Bukit Camat Office. Human capital has a positive influence on organizational change at the Pesisir Bukit Camat Office. Organizational culture, leadership, and human capital together have a positive effect on organizational change at the Pesisir Bukit Camat Office.